Geopolitical Dimension of Nepal and its Impact in South Asia - Bhattarai, Umesh K. (Journal of International Affairs, 2016)
International security and its relevancy to nation’s stability are heavily influenced by the geo-political situation of a country. By geo-politics, it is a relationship among politics, geography, demography, and economics-especially in respect to foreign policy adopted by a nation within the region. It dictates the overall governmental policies. In other words, the power relationship is dictated by the geographic location of the country. Geo-politics is the study of the political and strategic relevance of geography in a pursuit to national and international power (Khanal, 2011). So, the location and the physical environment are important factors to decide international power structure of a nation in the global as well as in regional context. Geo-strategy is a branch of geo-politics that deals with strategy. It characterizes a certain geographic area that affects the analysis of a region (Dahal, 2009). In order to understand the importance of geo-strategy of Nepal, we need to understand geographical context of the Indian subcontinent as a whole. It is a self-contained region that includes India, Pakistan, Bangladesh, Nepal and Bhutan. We may call the subcontinent “self-contained” because it is a region that is isolated on all sides by difficult terrain or by ocean. In geopolitical terms it is– an island (Friedman, 2008).